Advancing modes of equity participation in Islamic finance: problems and measures - Sadique, Muhammad Abdurrahman (Zesdyzar Rokman Resources, 2015)
Facilitating equity participation in trade and other undertakings that help the real fruits of ventures spread among a larger segment of the society while dividing the inherent risk is an important facet of an Islamic financial system. Several decades after their appearance in the scene of banking and finance, Islamic banks continue to use debt-financing tools widely, and have not so far been successful in implementing equity modes in a significant manner. The reality of equity financing becoming merged with debt-oriented practices due to erroneous or weak structures gaining currency may prove harmful to the cause of Islamic finance in the long-term. Many equity formats in vogue embody features that inhibit them from optimum performance. With growing awareness of the negative facets of debt financing, scope for equity modes could expand in the near future. It is essential that necessary guidelines are laid down and complexities dealt with in time for ready application. The paper explores problems related to implementing equity based structures, and highlights the measures to be adopted for advancement of equity financing.